The mythic dream - Parisien, Dominik; Wolfe, Navah; McGuire, Seanan; Leckie, Ann; Kingfisher, T.; Roanhorse, Rebecca; Yang, J. Y.; Martine, Arkady; Gailey, Sarah; Hernandez, Carlos Alberto; Jones, Stephen Graham, 1972-; Howard, Kat (Saga Press, 2019)
The Mythic Dream gathers together 18 stories that reclaim the myths that shaped our collective past, and use them to explore our present and future. From Hades and Persephone to Kali, from Loki to Inanna, this anthology explores retellings of myths across cultures and civilizations.